Information-algorithmic basis of a program complex for forest fire danger estimation - Engel M. V. Marina Vladimirovna; Belov V. V.; Baranovskiy N. V. Nikolay Viktorovich; Yankovich E. P. Elena Petrovna (Optical Investigation of Atmosphere and Ocean, 2016)
Title screen